Employee Performance: Exploring Transformational Leadership, Organizational Culture, and Employee Engagement as a Mediator in Micro, Small, and Medium Enterprise Food Sector - Nurimansjah, Ris Akril; Erwina, Erwina; Anggoro KR, M. Yusuf Alfian Rendra; Hamid, Mansoor Abdul (Universitas Brawijaya, Indonesia, 2024)
The increasingly tight competition in the MSME sector requires organizations to implement an effective leadership style and build a strong organizational culture to improve employee performance. This is an urgency for MSMEs to adapt and increase employee engagement as an important factor in creating competitive advantage. This study aims to examine the impact of Transformational Leadership and Organizational Culture on employee performance, with employee engagement acting as a mediating variable. Transformational Leadership and Organizational Culture are considered important in improving employee performance by encouraging greater engagement in the workplace. This study uses a quantitative approach with a population of all UMKM actors in the Food Sector in Jatinangor District totaling 133 people. Sampling was carried out using purposive sampling so that a sample size of 100 people was obtained. The results of the study indicate that transformational leadership does not have a significant direct effect on employee performance or employee engagement. Transformational leadership is proven to have a significant effect on employee engagement. Organizational culture also has a significant effect on employee engagement. Employee engagement has a positive effect on their performance. Employee engagement also mediates the relationship between transformational leadership and performance, as well as between organizational culture and performance. Organizational culture does not directly affect performance, building a positive culture is still important to increase employee engagement.